FIR filter design using modified lanczos window function - Samad, Md. Abdus; Uddin, Jia; Ahmed, Md. Razu (© 2012 Advanced Materials Research, 2016)
This conference paper was presented in the International Conference on Machine Design and Manufacturing Engineering, ICMDME 2012; Jeju Island; South Korea; 11 May 2012 through 12 May 2012 [© 2012 Trans Tech Publications, Switzerlandt] The conference paper's definite version is available at: :http://dx.doi.org/10.4028/www.scientific.net/AMR.566.49